2014
DOI: 10.1186/1476-511x-13-98
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin helps preserve pancreatic β cell function in obese C57BL/6 J mice and the effect is related to increased pancreas proliferation and amelioration of endoplasmic-reticulum stress

Abstract: Background3-Hydroxy-3-methyl-glutaryl CoA (HMG-CoA) reductase inhibitors or statins are competitive inhibitors of the rate-limiting enzyme in cholesterol biosynthesis. Currently, statins are used as first-line therapy in the treatment of diabetic dyslipidemia. However, effects of statins on β cell function remains unclear. This study aims to examine effects of atorvastatin treatment on pancreatic β cell function in obese C57BL/6 J mice and the possible mechanisms.MethodsDiet-induced obesity (DIO) C57BL/6 J mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 44 publications
(46 reference statements)
3
26
0
Order By: Relevance
“…These pleiotropic effects of atorvastatin which led to the adjustment of glucose homeostasis and renoprotection observed in this study might be due to the additive effect of atorvastatin and insulin in controlling metabolic parameters and subsequently protect kidney dysfunction in diabetes. This proposed mechanism is supported by the previous study reporting that atorvastatin can increase β-cell function by increasing β-cell proliferation and decreasing ER stress conditions 33 . The increased insulin secretion and the attenuation of apoptosis of pancreatic tissue seen in rats on the combined treatment in this study reflected an improvement in β-cell function.…”
Section: Discussionsupporting
confidence: 81%
“…These pleiotropic effects of atorvastatin which led to the adjustment of glucose homeostasis and renoprotection observed in this study might be due to the additive effect of atorvastatin and insulin in controlling metabolic parameters and subsequently protect kidney dysfunction in diabetes. This proposed mechanism is supported by the previous study reporting that atorvastatin can increase β-cell function by increasing β-cell proliferation and decreasing ER stress conditions 33 . The increased insulin secretion and the attenuation of apoptosis of pancreatic tissue seen in rats on the combined treatment in this study reflected an improvement in β-cell function.…”
Section: Discussionsupporting
confidence: 81%
“…Comparing the mean values of % of caspase 3 +ve cells in A treated group to AM group, it was significantly decreased. Chen et al ( 32 ) reported decreased apoptotic rate in A treated rats evidenced by flow cytometry analysis. Western blot additionally displayed that atorvastatin induced up regulation of anti-apoptosis protein Bcl-2.…”
Section: Discussionmentioning
confidence: 99%
“…Western blot analysis of total protein was performed as previously described [ 13 , 14 ]. Approximately 150 mg of liver, small intestine and kidney tissue were used to extract protein for each assay respectively.…”
Section: Methodsmentioning
confidence: 99%